INCREASING STUDENTS’ WRITING SKILLS BY UTILIZING BLOGS - Akhmad Fauzan (LET: Linguistics, Literature and English Teaching Journal)
There were four major problems related to writing instruction at English Education Study Program of Palangka Raya University, Central Kalimantan, Indonesia. The problems were related to limited sources of printed materials, mostly teacher-centered activities, readers of students’ writings, and feedbacks for students’ writings. The utilization of blogs was performed to solve the problems. Blog was used as media in this research because it is a potential source for language learning, student fit, authentic for learning, and practical to apply. The research design was Classroom Action Research (CAR). There were 2 cycles implemented during this research. In the first cycle, the students’ writing improvement did not show significant progress and the criterion of success was not achieved. After the plan was revised on the basis of the findings during the implementation of first cycle, 80% students showed great improvements. Therefore, the criterion of success was achieved.